Intermetallic and leaching study of (sn-8zn-3bi)-1ag lead-free solder / Nor Aishah Jasli - Jasli, Nor Aishah (2016)
Due to the health concerns, the demand for Pb-free solder is greater than before. In the past, Sn-Pb solders were widely used in soldering process due to their excellent soldering characteristics and reliability. Pb-free solder, the Sn-8Zn-3Bi eutectic alloy is regarded as one of the best potential candidates. This study investigated the effect of silver (Ag) addition on morphology, growth rate ofCu5Zn8, Cu6Sn5 and Cu3Sn intermetallics in the Sn-8Zn-3Bi solder. Besides that, leaching activities of heavy metal from solder alloys are also observed. Firstly, when the mixing process occured, the addition of Ag into the Sn-8Zn-3Bi solder has increased the melting temperature from 202°C to 228.19°C. After that, the reflow was done at 220°C, 230°C, 250°C, 270°C and 290°C at various soldering times. The Sn-8Zn-3Bi solder reacting with Cu substrate formed a single Cu5Zn8 intermetallic layer with a flat structure. On the other hand, the reaction between (Sn-8Zn-3Bi)-1Ag solder and Cu substrate produces Cu6Sn5and Cu3Sn intermetallic and both intermetallic has a scallop structure. The thickness of the intermetallics increases with aging temperatures and time. The addition of Ag into the Sn-8Zn-3Bi solder has significantly suppressed the formation of Cu5Zn8 intermetallic, and promoted the growth of Cu6Sn5 and Cu3Sn intermetallic. Growth rate constant of Cu5Zn8 phase is lower at low temperature and increase at high temperature, but only before the addition of Ag into solder system. Meanwhile the growth rate constant of Cu6Sn5 is bigger than Cu3Sn phase, thus providing an opportunity for Cu6Sn5 phase to predominate the total intermetallic compounds in this liquid-state aging study. Activation energy obtains for Cu5Zn8 phase was 78.54kJ/mol meanwhile for Cu6Sn5 and Cu3Sn phase is 266.72kJ/mol and 27.14kJ/mol each. In leaching of heavy metals, Sn was detected as the most leached heavy metals from solder alloy followed by Zn element. In this leaching process electrochemical and galvanic reaction contributes to the corrosion process that occurs in the bulk solder and solder joint.